Increasing driving range for electric vehicles at sub-zero temperatures by optimizing a hybrid storage configuration using supercapacitors (2020)
One of the main challenges electric vehicles manufacturers face is the perceived limited operational range of cars, commonly referred to as "range anxiety". Furthermore, effective range in these vehicles is affected by multiple factors, including driving behavior, battery size, operating temperature, among others. Particularly, Lithium-based batteries the most used in the industry today, experience significant electrochemical changes when operating at sub-zero temperatures, which reduces their overall energy capacity. Furthermore, cycling operation under these conditions, could also severely reduce the batteries' expected lifetime. This work uses a model-based approach to simulate a reduced current rate from lithium-based batteries, operating at sub-zero temperatures, during high-acceleration modes by including super-capacitors. By adding super-capacitors, the power supplied to the motors from the battery pack during short-time acceleration periods, can be reduced. This approach suggests that the effective range in Electric Vehicles increases by using an optimal hybrid energy storage system. Simulations were carried out to estimate the impact of subzero temperatures on the range of the vehicle. Results showed that the overall range increases with the addition of the the storage system. Furthermore, reduced current rates at sub-zero temperatures would also increase the battery pack's expected lifetime. These results offer great insights for designing more efficient energy storage systems for electric vehicles.